(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The antitumor, analgesic and anti-inflammatory activities of the methanol extract (MEGM) of Glochidion multiloculare and its petroleum ether (PEFGM), carbon tetrachloride (CTFGM) and chloroform (CHFGM) soluble fractions were investigated. The antitumor activity of the extract/fractions was determined against Ehrlichs ascites carcinoma (EAC) in mice at 20 mg/kg body weight intraperitoneally. Increase of survival time by 24 ± 0.12, 26 ± 0.40, 21 ± 0.12 and 27 ± 0.42 days was observed by the MEGM, PEFGM, CTFGM and CHFGM treated tumor bearing mice compared to the control group (20 ± 0.12 days). Hematological studies revealed that heamoglobin (Hb) content was decreased in EAC treated mice whereas restoration to normal levels was observed in extract/fractions treated animals. Significant decrease in RBC and increase in WBC counts were observed in extract/fractions treated animals when compared to EAC affected animals. Both extract and fractions at the dose of 100 mg/kg b.w. significantly increased the pain threshold in tail immersion method and reduced the writhing caused by acetic acid induced method. The MEGM, PEFGM, CTFGM and CHFGM showed anti-inflammatory activities at 100 mg/kg b.w. This is the first report of antitumor, analgesic and anti-inflammatory potential of G. multiloculare. Bangladesh Pharmaceutical Journal 18(2): 142-148, 2015